DEVELOPMENT TRAINING MULTIMEDIA TAVAGI BASED on SCIENCE TO SUPPORT 2013 CURRICULUM on TEACHERS IPA of RAYON 1 PASAMAN DISTRICT - Hufri Hufri (Pelita Eksakta, 2019)
ABSTRACT . The PKM activity aims to improve the competence of science teachers at Rayon 1 Pasaman junior high school in developing scientific-based interactive multimedia to support the 2013 curriculum. The target to be achieved is to increase the competency of teachers in developing TAVAGI multimedia (Text, Audio, Video, Animation, Graph , and interactivity) are science based. To achieve the goals and targets set, the method used consists of the observation phase, the orientation and discussion phase, the preparation stage of implementation, the implementation phase, the monitoring and evaluation stage as well as the data analysis and report making stage. The instrument used was a test on TAVAGI multimedia and a questionnaire for the implementation of activities. The results of data analysis of pretest and posttest, obtained an increase in the average pretest value of 34.28, and the average posttest score was 44.77 indicating the average value, posttest was higher than the pretest value. From the paired t test, the significance results obtained 0.000 <0.05. So it can be concluded that the PKM activities have been able to increase the competence of the teachers of Pasaman Rayon 1 Natural Science in developing scientific-based interactive multimedia to support the 2013 curriculum. very useful and related to learning in school.